Synchrotron infrared microspectroscopy study of the orientation of an organic surfactant on a microscopically rough steel surface - Lepkova, Katerina; Van Bronswijk, Wilhelm; Pandarinathan, Vedapriya; Gubner, Rolf (Elsevier Science BV, 2013)
The performance of organic surfactants as corrosion inhibitors is influenced by the mechanism of adsorption and the resulting molecular orientation on the substrate. The molecular orientation of 1-dodecylpyridinium chloride (DPC) deposited on non-corroded 1030 mild steel and after corrosion in a carbon dioxide environment has been investigated using synchrotron infrared microspectroscopy. DPC mitigates the corrosion process by adsorbing at the steel surface and forming a protective layer. Infrared spectra analogous to polarized grazing angle spectra were obtained from a microscopically rough surface using a synchrotron source. The appearance of negative and positive absorption bandsin the spectra, when using synchrotron radiation, is discussed in terms of the optical system used. The presence of the DPC surfactant at the steel surface is shown by the CH2 and CH3 infrared absorption bands of the aliphatic chain of the DPC molecule. The infrared spectra provide direct evidence on the orientation of DPC at the steel substrate. The aliphatic chain of the surfactant is tilted orthogonally, but not perpendicular to the substrate plane. The absence of significant absorption bands characteristic of the pyridinium ring of DPC indicates its orientation parallel to the substrate plane, and an adsorption mechanism involving pi-bonding with the steel. This study demonstrates the applicability of synchrotron infrared microspectroscopy to the investigations of thin organic films on microscopically rough steel surfaces, and can facilitate further investigations of thin films on metallic surfaces and monolayer studies in general.